INDEKS MASSA TUBUH (IMT) IBU HAMIL DENGAN KEJADIAN PREEKLAMSIA - Nurun Ayati Khasanah; Ferila Adiesti; Citra Adityarini Safitri (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2025)
Pre-eclampsia is a serious complication of pregnancy that can harm both mother and fetus. Several risk factors are known to influence the incidence of pre-eclampsia, one of which is Body Mass Index (BMI) which is associated with obesity and metabolic disorders. This study aims to analyze the relationship between BMI and the incidence of pre-eclampsia in pregnant women at Bangil Pasuruan Hospital. Methods: This study used an analytic design with a cross-sectional approach. Data were obtained through the medical records of pregnant women who underwent examinations at Bangil Hospital. The study sample consisted of 84 pregnant women who met the inclusion and exclusion criteria. BMI data was calculated based on the mother's weight and height, while the diagnosis of pre-eclampsia was determined through medical examination according to applicable criteria. The analysis showed a p value = 0.003, indicating a significant association between BMI and the incidence of pre-eclampsia in pregnant women. This indicates that pregnant women with higher BMI have a greater risk of developing pre-eclampsia. The conclusion of this study is that BMI is a significant risk factor for the incidence of pre-eclampsia in pregnant women at Bangil Pasuruan Hospital. Therefore, it is important to monitor and manage weight in pregnant women as part of efforts to prevent pre-eclampsia.